Kinetics of a packed-bed bacth reactor for the treatment of olive oil wastewaters from a Portuguese mill - Ribeiro, Belina (2010)
Olive oil production is a traditional agricultural industry in Mediterranean countries and Portugal is one of the ten major producers. This industry generates an effluent, olive mill wastewater. This effluent does not undergo any treatment and is usually stored in evaporation lagoons or spread on the land. This can have a negative impact in the environment since this effluent has a high level of organic matter leading to a high chemical oxygen demand. In addition it has also a high content of polyphenols that contributes to the ecotoxicity of this effluent.Different techniques for the treatment of these wastewaters have been studied. In this work a 60 litre vessel was filled with a packaging of plastic material consisting of a cubic geometry (Biological Carrier Media from Rauschert). The non-inoculated reactor was filled with effluent from an olive mill farm (from Alfândega da Fé, Trás-os-Montes) and the effluent was re-circulated daily for homogeneity. COD, colour, nitrogen, solids and phosphorous were measured to follow the evolution of the system. Microbial composition and polyphenols were also evaluated. As an indicator of the microbial activity in the reactor, lipase activities were measured. Ecotoxicity tests were carried out to follow the detoxification capacity of the system as well as its potential for using in the treatment of this type of agroindustrial effluent.